MYC-Induced miR-203b-3p and miR-203a-3p Control Bc1-xL Expression and Paclitaxel Sensitivity in Tumor Cells - Aakko Sofia; Straume Anne Hege; Birkeland Einar Elvbakken; Chen Ping; Qiao Xi; Lønning Per Eystein; Kallio Marko J. (ELSEVIER SCIENCE INC, 2022)
Taxanes are chemotherapeutic agents used in the treatment of solid tumors, particularly of breast, ovarian, and lung origin. However, patients show divergent therapy responses, and the molecular determinants of taxane sensitivity have remained elusive. Especially the signaling pathways that promote death of the taxane-treated cells are poorly characterized. Here we describe a novel part of a signaling route in which c-Myc enhances paclitaxel sensitivity through upregulation of miR-203b-3p and miR-203a-3p; two clustered antiapoptosis protein BcI-xL controlling microRNAs. In vitro, the miR-203b-3p decreases the expression of BcI-xL by direct targeting of the gene's mRNA 3'UTR. Notably, overexpression of the miR-203b-3p changed the fate of paclitaxel-treated breast and ovarian cancer cells from mitotic slippage to cell death. In breast tumors, high expression of the miR-203b-3p and MYC was associated with better therapy response and patient survival. Interestingly, in the breast tumors, MYC expression correlated negatively with BCL2L1 expression but positively with miR-203b-3p and miR-203a-3p. Finally, silencing of MYC suppressed the transcription of both miRNAs in breast tumor cells. Pending further validation, these results may assist in patient stratification for taxane therapy.